Does tinnitus "fill in" the silent gaps? - Jennifer Campolo; Edward Lobarinas; Richard Salvi (Noise and Health, 2013)
In the basic sciences, many researchers now use gap pre-pulse inhibition of the acoustic startle reflex (GPIAS) to determine if an animal has tinnitus after exposure to an ototoxic drug or intense noise. Tinnitus is assumed to be present if the silent gap in an ongoing narrow band noise (NBN) fails to suppress the startle reflex response evoked by an intense noise burst. The lack of gap pre-pulse inhibition presumably occurs because tinnitus fills in the silent intervals in the background noise. To test the perceptual aspects of this hypothesis, we asked hearing impaired subjects with tinnitus if they could perceive 50 ms silent intervals presented in a NBN, which was located above, below or at the subject′s tinnitus pitch. The same tests were performed on normal hearing subjects without tinnitus. All subjects, with and without tinnitus, could detect the 50 ms gaps. Thus, using the stimulus parameters similar to those employed in animal and human GPIAS studies, we found that the tinnitus percept does not fill in the silent interval in a perceptual gap detection task; however, these finding do not rule out the possibility that tinnitus interferes with pre-attentive filtering of sensory stimuli in the GPIAS sensorimotor gating paradigm.